2015
DOI: 10.1007/112_2015_27
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiology and Pharmacologic Modulation of the Renin–Angiotensin–Aldosterone System in Dogs: What Have We Learned?

Abstract: Congestive heart failure (CHF) is a primary cause of morbidity and mortality with an increasing prevalence in human and canine populations. Recognition of the role of renin-angiotensin-aldosterone system (RAAS) overactivation in the pathophysiology of CHF has led to significant medical advances. By decreasing systemic vascular resistance and angiotensin II (AII) production, angiotensin-converting enzyme (ACE) inhibitors such as benazepril improve cardiac hemodynamics and reduce mortality in human and dog CHF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 146 publications
1
26
0
Order By: Relevance
“…Another limitation is the potential effects of chronobiology and diet on the RAAS and NP system. Circadian fluctuations of RAAS hormones and dietary sodium content could have affected our results, but intrapatient variables (feeding times, food types, sample collection times) were held constant for the duration of the study period 55, 56. Pooled urine samples also were used to minimize the potential effect of these variables on urinary aldosterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the potential effects of chronobiology and diet on the RAAS and NP system. Circadian fluctuations of RAAS hormones and dietary sodium content could have affected our results, but intrapatient variables (feeding times, food types, sample collection times) were held constant for the duration of the study period 55, 56. Pooled urine samples also were used to minimize the potential effect of these variables on urinary aldosterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the higher serum sodium concentrations observed in Greyhounds, suggesting that aldosterone secretion is downregulated. If ACE activity reflects angiotensin II production, this would suggest that direct renal effects of angiotensin II on tubular sodium reabsorption could be more important than those of aldosterone in maintaining the higher serum sodium concentrations in the Greyhounds . While chronic infusion of angiotensin II into the renal artery of Greyhounds results in increased systemic arterial pressure, baseline levels of angiotensin II have not been measured in this breed .…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent report from the National Academy of Medicine (64), only one out of ten oncology candidates that appear promising in preclinical mouse models are in fact effective and safe in human clinical trials. This overtly high attrition rate highlights the need for alternative models at the early stage of the Drug Research and Development lifecycle (65), as shown in other therapeutic areas (66)(67)(68)(69)(70)(71).…”
Section: Comparative Oncology: An Opportunity To Accelerate Parallel mentioning
confidence: 99%